Predictor variables for post-discharge mortality modelling in infants: a protocol development project - Nemetchek, Brooklyn R; Liang, Li(Danny); Kissoon, Niranjan; Ansermino, J Mark; Kabakyenga, Jerome; Lavoie, Pascal M; Kerry, Susan Fowler; Wiens, Matthew O (African Health Sciences, 2018)
Background: Over two-thirds of the five million annual deaths in children under five occur in infants, mostly in developing countries and many after hospital discharge. However, there is a lack of understanding of which children are at higher risk based on early clinical predictors. Early identification of vulnerable infants at high-risk for death post-discharge is important in order to craft interventional programs. Objectives: To determine potential predictor variables for post-discharge mortality in infants less than one year of age who are likely to die after discharge from health facilities in the developing world. Methods: A two-round modified Delphi process was conducted, wherein a panel of experts evaluated variables selected from a systematic literature review. Variables were evaluated based on (1) predictive value, (2) measurement reliability, (3) availability, and (4) applicability in low-resource settings. Results: In the first round, 18 experts evaluated 37 candidate variables and suggested 26 additional variables. Twenty-seven variables derived from those suggested in the first round were evaluated by 17 experts during the second round. A final total of 55 candidate variables was retained. Conclusion: A systematic approach yielded 55 candidate predictor variables to use in devising predictive models for post-discharge mortality in infants in a low-resource setting.
Keywords: Candidate predictor variables; Pediatrics; Neonatal; Infants; Prediction; Post-discharge mortality; Sepsis